PENGEMBANGAN E-LKPD BERDIFERENSIASI BERBASIS PjBL (PROJECT BASED LEARNING) BERBANTUAN QR CODE PADA MATERI PELUANG - Yugi Ananda Saputra; Rahmi; Mulia Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low level of student engagement and understanding in mathematics learning, particularly in probability, due to the limited use of teaching materials, which are limited to printed textbooks and have not been integrated with technology. Students require interactive, engaging, and easily accessible teaching materials to support differentiated learning in the Independent Curriculum. This research aims to develop a valid and practical Project-Based Learning (PjBL)-based differentiated electronic student worksheet (LKPD) with QR codes for use in mathematics learning on probability. This research is a Research and Development (R&D) study using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects included a mathematics educator and 14 tenth-grade students from SMA Negeri 1 Rambatan, with both high and low abilities. The research instruments included a characteristic questionnaire, validation sheet, practicality questionnaire, and interview guide, which were analyzed quantitatively and qualitatively. The results showed that the developed electronic student worksheet achieved a validity score of 90.8% (categorized as very valid). The practicality score was 94.17% from teachers and 90% from students (very practical category). Thus, the QR Code-assisted PjBL-based e-LKPD is declared valid, practical, and suitable for use as a mathematics learning medium for probability.